Diagnostic utility of histopathological patterns of endometrium in abnormal uterine bleeding and its correlation with age -a two years study at a rural Tertiary care hospital in south india - DR.REVATHY S; DR.VAISHALI D KOTASTHANE; DR.DHANANJAY S KOTASTHANE; DR.SHANMUGASAMY K (International Journal of Pharma and Bio Sciences, 2017)
Abnormal uterine bleeding (AUB) is a common gynaecological disorder in women of all ages caused by a wide variety of disorders. Aim of the present study was to know the different endometrial lesions in cases of AUB reported in rural tertiary care hospital and its correlation with age of presentation. This was a descriptive study which was conducted at a rural tertiary care hospital in Pondicherry. Study included endometrial curettage / hysterectomy specimens pertaining to AUB, received for a period of two years in department of pathology. Representative sections of endometrium and myometrium were taken from hysterectomy specimens and endometrial curettage were processed as a whole and slides were stained with haematoxylin and eosin. Endometrial tissues of 600 cases were studied. Age of the patient varied from 18 to 73 years. Peak incidence was seen in perimenopausal women (36-49 years). Different histopathological patterns of endometrium were observed, Normal cyclical pattern (62.8%) were more commonly seen followed by Pregnancy related complications(10.7%), disordered proliferative phase (9.5%), Endometrial hyperplasia (5.4%), Hormonal imbalance (4.3%), Benign endometrial polyp (3.6%),Atrophic endometrium (1.5%), Endometrial adenocarcinoma of endometrioid variant (1.3%), Endometritis (0.6%), Arias stella reaction (0.2%) and Pyometra (0.2%). Endometrial biopsy/ curettage are the two most important sampling methods for definitive diagnosis of endometrial pathology which can result in tailor made management of AUB, leading to rational surgical or medical intervention. In addition , it can lead to early detection and diagnosis of preneoplastic/neoplastic conditions that can minimise patient’s morbidity/mortality.